2020
DOI: 10.1016/j.cegh.2020.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Contraceptives utilization and barriers in Karnataka, Southern India: A survey on women residing in slums

Abstract: Background: Population explosion remains a major cause of concern in India. Although, the country became the first to implement a national population control programme in 1952, it is yet to effectively control its population growth. Methods: A community-based cross-sectional survey was conducted to assess the utilization and barriers for nonutilization of contraceptives among slum resident married women of Udupi district, Karnataka, India between October 2017 to July 2018 The survey involved 323 married women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
1
3
0
Order By: Relevance
“…High levels of unmet need for family planning and unintended pregnancies continue to persist, indicating the presence of barriers that hinder the effective use of contraception. The barriers identified by this study are in agreement with other studies that have cited similar [13][14][15]19 reasons for the non-utilization of contraception.…”
Section: Julysupporting
confidence: 91%
“…High levels of unmet need for family planning and unintended pregnancies continue to persist, indicating the presence of barriers that hinder the effective use of contraception. The barriers identified by this study are in agreement with other studies that have cited similar [13][14][15]19 reasons for the non-utilization of contraception.…”
Section: Julysupporting
confidence: 91%
“…This is also supported by the ndings from a study done in Kenya which found that the preference for boys was the reason why families with few boys and many girls avoid using contraceptives. Similarly, low contraceptive utilisation due to a desire for boys over girls was also con rmed in a study done in India [75].…”
Section: Preference For Boys For Wealth Inheritancementioning
confidence: 62%
“…While most individuals in the region are familiar with at least three types of family planning (FP) methods, there is a gap in preparedness for future use or guidance from others. Despite awareness of modern contraceptives, a limited percentage of women possess knowledge about family planning methods, as evidenced by previous studies (Swamy et al, 2017) (Mishra et al, 2017), (Ochako et al, 2018), (Palo et al, 2020), (Mushy et al, 2020), and (Sowmya et al, 2020), (Sekine et al, 2021). (Prusty, 2014) reported that even though tribal women were aware of FP methods in Jharkhand, only 17% utilized any modern contraception, in contrast to 39% of nontribal women.…”
Section: Discussionmentioning
confidence: 96%